Evaluation of The Implementation of The Alternaive X Tourism Strategy As The Implementation of The Strategic Plan For The Tourism Service of The Province of Jatim 2016 -2021 - Tri Cicik Wijaya (INNOVATION RESEARCH JOURNAL, 2021)
here is only one analytical technique at the decision stage in strategy formulation to determine the relative attractiveness and appropriate alternative actions. The technique is the Quantitive Strategic Planning Matrix (QSPM) which forms stage 3 of the formulation strategy. QSPM is a tool that enables strategists to evaluate internal key factors. Conceptually, the QSPM determines the relative attractiveness of various strategies from the extent to which key internal and external success factors are utilized or enhanced. This research begins by analyzing the Kebon Agung village, Ujung Pangkah sub- district and the SME development plan, followed by implementing the next model, the implementation of the strategy model can be reconstructed according to the conditions of development. There is only one analytical technique at the decision stage in strategy formulation to determine the relative attractiveness and appropriate alternative actions. The technique is the Quantitive Strategic Planning Matrix (QSPM) which forms stage 3 of the formulation strategy. QSPM is a tool that enables strategists to evaluate internal key factors. Conceptually, QSPM determines the relative attractiveness of various strategies from the extent to which key internal and external success factors are utilized or enhanced. Regarding HR strategy.